A meaning holistic (dis)solution of subject–object dualism – its implications for the human sciences - Piiroinen Tero (SAGE, 2022)
This article presents and analyses a social-practice contextualist version of meaning holism, whose main root lies in American pragmatism. Proposing that beliefs depend on systems of language-use in social practices, which involve communities of people and worldly objects, such meaning holism effectively breaks down the Enlightenment tradition’s philosophical subject–object dualism (and scepticism). It also opens the human mind up for empirical research – in a ‘sociologizing’, ‘anthropologizing’ and ‘historicizing’ vein. The article discusses the implications of this approach for the human sciences, for instance certain parallel developments in anthropology and archaeology.